The Effectiveness of Adolescent-Centered Mindfulness Training on Academic Burnout and Symptoms of Social Anxiety in Students - Sanaz Soolari Esfahani; Seyed Hamid Atashpour; Narges Keshti Arai; Ali Mahdad (پژوهش‌های کاربردی روانشناختی)
The aim of this study was to investigate the effectiveness of adolescent-centered mindfulness training on academic burnout and symptoms of social anxiety in female high school students. The study method was quasi-experimental, utilizing a pre-test-post-test design. The control group underwent a baseline assessment after the intervention, followed by a three-month follow-up. The statistical population comprises all female high school students who were enrolled in the 2019-2020 academic year and exhibited symptoms of social anxiety. Purposive sampling was employed to select 30 female students, who were subsequently randomly assigned to two experimental and control groups, each consisting of 15 individuals. The instruments of this study were researcher-made demographic questionnaire, Social Anxiety Questionnaire (SAQ) and f Maslach Burnout Inventory Student Survey (MBI-SS) and Adolescent-Centered Mindfulness Protocol (ACMP). The spss variance21 was analyzed using repeated measures. The results showed that adolescent-centered mindfulness training had a significant effect on reducing academic fatigue and symptoms of social anxiety in female high school students (p <0.001). Consequently, female high school students who engaged in mindfulness training sessions that were centered around adolescents experienced a decrease in their levels of social anxiety and academic burnout. Therefore, adolescent-centered mindfulness training has a significant effect onacademic burnout and students’ social anxiety symptoms.